Critical factors impacting interdisciplinary university research teams of small size: A multiple-case study. Issue 1 (12th March 2020) - Tkachenko, Oleksandr; Ardichvili, Alexandre
Abstract : Purpose: This study aims to explore key factors influencing the work of interdisciplinary university research teams of small size. Design/methodology/approach: This is a multiple-case study of four interdisciplinary university research teams of small size in which science and/or engineering was an important component. Findings: Data analysis revealed 17 critical factors classified into five groups. Although some factors were more influential than others, it was rather multiple factors at various levels of analysis, and not a single factor, that influenced the work of research teams. Another important finding was the identified need to develop project management capacity of university researchers. The study also revealed two strategies, conditioned on the availability of funds, that small university research teams use as a way to adapt to situational demands and research opportunities. Originality/value: Although previous research examined various aspects pertinent to the work of industry research teams and large research groups, empirical research into interdisciplinary university research teams of small size has been limited.